Choreography : a basic approach using improvisation - Minton, Sandra Cerny, 1943- 4 0 16; 5 (Champaign, IL : Human Kinetics, 2007)
Discusses improvisation of movement, the design and shape of dance, choreographic form and development, and examples of the use of multimedia technology to enhance performances with lighting effects, slide and PowerPoint projections, motion capture, and more, and includes exploration exercises and reflection questions.
Includes bibliographical references (p. 156-158) and index.
Adult;Adult
Keywords: 2 -- 0; 6; Choreography.;Choreography.; 20; 2